Director's age diversity and firm performance: A new perspective - Malek, Mazrah; Che Ahmad, Ayoib; Fauzi Saidin, Saidatunur (Macrothink Institute, 2021)
Diversity of board members has become a recent topic by which it has been linked to board’s effectiveness. It can be postulated that directors from a different generation will exhibit different values, knowledge and behavior that can influence the decisions and actions of a firm. However, earlier studies have produced mixed findings on the effect of director's age and firm performance. This study proposes that in order to examine the influence of age diversity, researchers must capture the difference in the age cohort of directors. Different generations carry its own common and unique characteristics. Consistent with the diversity concept, age diversity should be examined based on the inclusion of different generations to the board, and not just the average number of directors’ age as practiced in earlier studies.